P-A8 Establishing tissue reservoirs for the human immunodeficiency virus in humanized mice. (April 2018) - Su, Hang; Dash, Prasanta; Gorantla, Santhi; Poluektova, Larisa; Gendelman, Howard
Abstract : Due to extraordinary challenges of early viral detection and restricted access to anatomical sites, it remains imperative to track early temporal dynamics of viral latency establishment. The development of humanized mice has provided new insights into the immunology, pathogenesis, treatment, prevention, and measured eradication. In the current study, we applied 2 widely used humanized mouse models of HIV/AIDS; human CD34+ hematopoietic stem cells (HSC) and peripheral blood lymphocytes (hu-PBLs)-transplanted NOD.Cg-Prkdcscid Il2rgtm1Wjl/SzJ mice, to investigate early events in HIV latency. Twenty hu-HSC or hu-PBLs mice were injected intraperitoneally with HIV-1 ADA at 104 TCID50. Infected animals were randomly separated into 4 groups and sacrificed at day 3, 5, 7 and 14 after infection. Blood and tissues were harvested for immunohistochemistry and semi-nested PCR tests for HIV-1 DNA and RNA. Peripheral CD4+ T cells were reduced by around 10% after HIV-1 infection in hu-HSCs mice but over 20% in hu-PBLs mice. IHC tests showed HIV-1p24 expressing cells only in 14-day infected hu-HSCs mice but in all infected hu-PBLs mice. HIV-1 RNA and DNA were observed in 14-day infected hu-HSCs mice from spleen lung liver and gut at 106-8 copies/106 hCD45+ cells, whereas detected in 2/5 animals (∼106 copies) at early time points. They were observed in all infected hu-PBLs mouse tissues (∼106copies/106 hCD45+ cells in 3-day group and 106-8 copies in other time points). HIV-1 was detected both hu-HSCs and hu-PBLs models as early as 3 days after infection but more robust within the latter. This may be related to various host restriction factors. Targeting these host factors may provide stronger clues about establishment of HIV persistence.